(untitled) (Third Sector Social Economic Review, 2024)
This research investigates the role of consumer ethnocentrism in shaping brand trust, emphasizing the mediating effect of consumer reshoring sentiment (CRS). It further examines how the country image of previously offshored nations, categorized as high or low, influences these dynamics, especially in the context of reshoring decisions. The study differentiates between reshoring decisions made during global crises versus stable periods. By integrating ethnocentrism, consumer reshoring responses, and offshored country perceptions, this work provides new insights into the external cues driving brand trust amid reshoring strategies and global uncertainties. A key finding is that during crises, consumers exhibit stronger preferences for domestically produced brands, resulting in elevated brand trust even when the company previously operated in a higher-image country. This study offers an integrative framework to understand the evolving consumer-company relationship amid reshoring in crisis contexts.